PENGENDALIAN MUTU PADA PRODUKSI KERIPIK SUKUN - Edi Junaidi; Banun Diyah Probowati; Muhammad Fakhry (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
There are many matter can be make chips. One of them is breadfruits chips. Consumers need a good quality of product. The industries must be keep the quality of its products. Therefore it is necessary for a good quality control on the quality control of raw materials, production processes and final products breadfruit chips. The aims of this study are to determine the application of the Seven Tools of Quality Control and how to improve product quality breadfruit chips. Analysis of quality control is done by using tools such as quality control check sheet, stratification, histograms, Pareto charts, scatter charts, fishbone diagram and control chart. Check sheets are used to present the data in order to facilitate the understanding of data to analyze further. P control chart is used to see whether a product is defective is well within control or not. The results of the data analysis showed that the p control chart product defects that occured during production process had upper threshold of 0.033 (79 pieces of breadfruit chip) and lower thresholdof 0.021 (50 pieces of breadfruit chip) with an average percentage per day damage of 2.765 % (66 pieces of breadfruit chip). Disability occurred once, because it exceeded the upper limit of the number of defects by 176 pieces of breadfruit chip (3.6%). Result of causative diagram analysis showed what factors causedproduct defects, those were raw materials, tools, production process, and human error. Result of this study can be used by the industry to immediately take corrective action to prevent and reduce the level of disability.